Development of Bis-Phenol A sensor based on Fe2MoO4·Fe3O4·ZnO nanoparticles for sustainable environment. Issue 1 (February 2018) - Subhan, Md Abdus; Saha, Pallab Chandra; Alam, M.M.; Asiri, Abdullah M.; Al-Mamun, Mohammad; Rahman, Mohammed M.
Graphical abstract: The proposed oxidation reaction of BPA by BPA chemical sensor based on Fe2 MoO4 ·Fe3 O4 ·ZnO/binder/GCE. Highlights: A versatile nano-molybdenum-iron-zinc-oxide (Fe2 MoO4 ·Fe3 O4 ·ZnO) nanoparticles has been synthesized. The nanoparticles were characterized by XRD, SEM, and FTIR and patticle size is 20.5 nm. The proposed chemical sensor Fe2 MoO4 ·Fe3 O4 ·ZnO of Bis-Phenol A (BPA) displays high selectivity with lower detection limit. The calibration plot is linear over the concentration range of 0.1 nM–1.0 mM of BPA. The calculated sensitivity is 292.7 μAmM −1  cm −2 with detection limit of 0.03 ± 0.0015 nM. Abstract: A versatile nano-molybdenum-iron-zinc-oxide (Fe2 MoO4 ·Fe3 O4 ·ZnO) nanoparticles (NPs) were prepared by co-precipitation method. The as-synthesized catalyst was characterized by several analytical techniques such as XRD, SEM, and FTIR spectroscopy. From the XRD pattern, particle size of the synthesized nanocomposite was calculated and found to be 20.5 nm. Elemental composition and their homogeneous distribution in Fe2 MoO4 ·Fe3 O4 ·ZnO was confirmed by EDS study. The proposed Bis-phenol (BPA) chemical sensor with active Fe2 MoO4 ·Fe3 O4 ·ZnO NPs displays good selectivity with lower detection limit (DL) and long-term stability with enhanced electrochemical response. The calibration plot is linear (r 2 : 0.9978) over the concentration range (LDR) of 0.1 nM–0.1 mM of BPA. The calculated sensitivity is 2.2468 μAμM −1  cm −2 with detection limit (DL) of 42.25 ± 2.11pM at signal to noise ratio of 3(S/N). The BPA chemical sensor fabricated with Fe2 MoO4 ·Fe3 O4 ·ZnO NPs may be a promising with high sensitivity in reliable I–V method. Thus, this novel effort initiates a well-organized way to the development of reliable Fe2 MoO4 ·Fe3 O4 ·ZnO NPs/binder/GCE chemical sensor for efficiently detection of real hazardous toxins in environment as well as healthcare sector in a broad scale.